Measurement of Ion Mobilities for the Ion-TPC of NvDEx Experiment - Tianyu Liang; Meiqiang Zhan; Hulin Wang; Xianglun Wei; Dongliang Zhang; Jun Liu; Chengui Lu; Qiang Hu; Yichen Yang; Chaosong Gao; Le Xiao; Xiangming Sun; et al. (Universe)
In the N<semantics>ν</semantics>DEx collaboration, a high-pressure gas TPC is being developed to search for the neutrinoless double beta decay. The use of electronegative 82SeF6 gas mandates an ion-TPC. The reconstruction of the z coordinate is to be realized by exploiting the feature of multiple species of charge carriers. As the initial stage of the development, we studied the properties of the <semantics>SF6</semantics> gas, which is non-toxic and has a similar molecular structure to <semantics>SeF6</semantics>. In the paper, we present the measurement of drift velocities and mobilities of the majority and minority negative charge carriers found in <semantics>SF6</semantics> at a pressure of 750 Torr, slightly higher than the local atmospheric pressure. The reduced fields range between 3.0 and 5.5 Td. This was performed using a laser beam to ionize the gas inside a small TPC, with a drift length of 3.7 cm. A customized charge-sensitive amplifier was developed to read out the anode signals induced by the slowly drifting ions. The closure test of the reconstruction of the z coordinate using the difference in the velocities of the two carriers was also demonstrated.